CD36 is Associated With the Development of Coronary Artery Lesions in Patients With Kawasaki Disease - Guo, Mindy Ming-Huey; Huang, Ying-Hsien; Wang, Feng-Sheng; Chang, Ling-Sai; Chen, Kuang-Den; Kuo, Ho-Chang (Frontiers in Immunology, 2022)
Kawasaki disease (KD) is an autoimmune-like vasculitis of childhood involving the coronary arteries. Macrophages require scavenger receptors such as CD36 to effectively clear cellular debris and induce self-tolerance. In this study, we hypothesized that CD36 plays an important role in the immunopathogenesis of KD, by aiding in the clearance of plasma mitochondrial DNA, and by amplifying the immune response by activating the inflammasome pathway via AIM2. Fifty-two healthy controls, 52 febrile controls, and 102 KD patients were recruited for RT-PCR of target mRNA expression and plasma mitochondrial DNA. Blood samples were obtained 24 hours prior and 21 days after the administration of intravenous immunoglobulin (IVIG) therapy. Patients with acute KD had higher plasma levels of cell-free mitochondrial DNA (ND1, ND4, and COX1), and higher mRNA expressions of CD36 and AIM2 when compared to both healthy and febrile controls. A greater decrease in both CD36 and AIM2 mRNA expression after IVIG therapy was associated with the development of coronary artery lesions. Coronary artery lesions were associated with a larger decrease of CD36 expression following IVIG therapy, which may indicate that prolonged expression of the scavenger receptor may have a protective effect against the development of coronary artery lesions in KD.